Relationship of Dietary Habits, Attitudes and Behaviors with Anthropometric Measurements in Adult Women - Dağ, Ayhan; Apaçi, Cansu; Kartal, Muhammed Enes; Coşkun, Aybüke (Progress in Nutrition, 2022)
Background and aim: This study aimed to determine relationship of dietary habits, attitudes and behaviors with anthropometric measurements in 300 women aged 19-65 years (150 employed women and 150 unemployed women) living in Lefkoşa, North Cyprus Turkish Republic between February, 2018 and June, 2020. Methods: In all subjects, data regarding sociodemographic characteristics, dietary habits and anthropometric measurements were recorded. All subjects completed  Eating Attitudes Test (EAT-26) and  Dutch Eating Behavior Questionnaire (DEBQ). Results: Mean body mass index (BMI) was 26.6±5.9 kg/m2 and 26.5±5.7 kg/m2 in employed and unemployed women, respectively. There was no significant difference in BMI based on employment status (p>0.05). Based on BMI, of the employed and unemployed woman, 48.7% and 40% were classified as normal while 26.6% and 35.3% as overweight and 24.7% and 24.7% as obese, respectively. It was found that emotional eating and restrained eating scores were increased by increasing BMI in both employed and unemployed women. A significant difference was found between BMI and emotional eating score in employed women (p